Re-thinking Gandhi : interrogation and exploration - Handique, Palash; Gohain, Monjit; Saikia, Hemanta (New Delhi : SSDN Publishers & Distributors, 2013)
Papers presented at a national seminar on "Rethinking Gandhi : interrogation and exploration" held at Golaghat on 12th September 2011
Includes bibliographical references and index
Keywords: Gandhi, Mohandas Karamchand, -- 1869-1948 -- Philosophy -- Congresses